Civilian participants in the Cultural Revolution : being vulnerable and being responsible - Mok, Francis K. T. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"In the ten years of the Cultural Revolution, political persecutions, violation of rights, deprivation of freedom, violence and brutality were daily occurrences. Especially striking is the huge number of ordinary civilians who were involved in inflicting pain and suffering on their comrades, colleagues, friends, neighbours, and even family members. The large-scale and systematic form of violence and injustice that was witnessed differs from that in countries like Chile under military rule or South Africa during apartheid in that such acts were largely committed by ordinary people instead of officials in uniforms. Mok asks how we should assess the moral responsibility of these wrongdoers, if any, for the harm they did both voluntarily and involuntarily. After the death of Chairman Mao, there was a trial of the Gang of Four, who were condemned as the chief perpetrators of the Cultural Revolution. Besides, tens of millions of officials and cadres who were wrongly accused and unfairly treated were subsequently cleared and reinstated under the new leadership. However, justice has not yet been fully done because no legal or political mechanism has ever been established for the massive number of civilian perpetrators to answer for all sorts of violence inflicted on other civilians, to make peace with their victims, and to make amends. The numerous civilians who participated need to come to terms with the people they wronged in those turbulent years. Justice in general and transitional justice in particular may still be pursued by taking the first steps to clarify and identify the moral burden and responsibility that may legitimately be ascribed to the various types of participant. This book will be of interest to anyone who studies the Cultural Revolution of China, especially those who are concerned with the ethical dimension."--
OCLC-licensed vendor bibliographic record.
Keywords: Mao, Zedong, -- 1893-1976 -- Influence; China -- History -- Cultural Revolution, 1966-1976.; China -- Social life and customs -- 1949-1976.